Making Our Mark: Labour Arts and Heritage in Ontario - Beveridge, Karl; Johnston, Jude (Between the Lines, 1999)
Finally, a book that documents the rich history of labour arts in Ontario. Making Our Mark presents over 100 projects, showcasing the vibrant banners, photos, plays and lyrics that form the heart and soul of the labour movement. Diverse examples spring from the Artist in the Workplace Program, the Mayworks Festivals, independent labour arts projects, and exhibitions organized the Ontario Workers Arts and Heritage Centre. Making Our Mark celebrates the songs of Arlene Mantle and Charlie Angus, photos by First Nations ironworkers, and dance performances by Tom Brouillette and the Boilermakers, to name a few.... Publisher's description
Keywords: Ontario